Two trade names of deferasirox (Osveral® and Exjade®) in reduction of iron overload parameters in major beta-thalassemia patients: A randomized open labeled clinical trial - Mohammadreza Rafati; Hossein Karami; Bita Lashtoo-Aghaee; Bahareh Lashtoo-Aghaee; Mojdeh Dabirian; Razieh Avan (Babol University of Medical Sciences, 2022)
Background: Beta-thalassemia major patients typically require chronic transfusion and iron-chelating agents to reduce serum iron overload. Osveral® is an available Iranian brand name of deferasirox used by majority of thalassemic patients. The aim of this study was to compare the efficacy of Osveral® vs. Exjade® in major beta- thalassemia patients. Methods: In this randomized clinical trial, all patients received a single daily dose of 30 mg/kg either of Osveral® or Exjade® for 6 months. Primary outcome was the mean of bimonthly changes in serum ferritin concentration and secondary outcomes included mean changes of heart and liver MRI T2* after a year. Results: Finally, 80 patients completed the study. The mean serum ferritin level at the end of sixth month significantly decreased in Osveral® and Exjade® groups (p<0.01). After a year, means cardiac MRI T2* in Osveral® group were changed from 25.9±9.6 ms to 25.4±9.7 ms and in Exjade® group from 24.8±9.2 ms to 26.9±5.9 ms, with no significant difference (P=0.43). Mean liver MRI T2* for Osveral® and Exjade® groups were 8.6±6.4 ms (baseline 6.3±4.7) and 6.3±4 ms (baseline 4.9±3.5), respectively and there was no significant difference between two study arms (P=0.1). Conclusion: Osveral® decreased significantly the serum ferritin level and improved heart and liver iron overload as efficient as Exjade®. It can be a suitable cost-effective alternative agent in beta-thalassemia major patients.